HUBUNGAN TINGKAT KECEMASAN DAN RESILIENSI DENGAN KEJADIAN IMPOSTOR PHENOMENON PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TAHUN 2022 - Anastasia Setiani (2022)
Impostor Phenomenon (IP) is a phenomenon in which high achievers doubt their abilities, attribute success to factors beyond their capabilities and fear being considered as a fraud. Impostor Phenomenon is associated with psychological attributes such as perfectionism, feelings of anxiety, depression, and low resilience. This study aims to determine the relationship between the level of anxiety and resilience with the occurrence of Impostor Phenomenon. The research design was in the form of observational analytics with a cross-sectional approach. The research sample was 99 students, through consecutive sampling methods using the State-Trait Anxiety Inventory, Connor Davidson Resilience Scale, and Clance Impostor Phenomenon Scale questionnaire. Univariate analysis showed 40 students (40.4%) with mild State Anxiety, 40 students (40.4%) with severe Trait Anxiety, 86 students (86.9%) with high resilience, and 57 students (57.6%) with high Impostor Phenomenon. Bivariate analysis using Chi-Square and Kendall's Tau-B test prove that there was a significant association between State Anxiety (p = 0.005; r = 0.303), Trait Anxiety (p = 0.000; r = 0.582) and resilience (p = 0.016; r = -0.273) with the occurrence of the Impostor Phenomenon. The results of multivariate analysis using multiple logistic regression showed that Trait Anxiety variable was the most dominant in influencing the occurrence of the Impostor Phenomenon (p = 0.000; OR = 0.042; 95% CI = 0.011 - 0.152).